2011
DOI: 10.1158/0008-5472.can-10-2330
|View full text |Cite
|
Sign up to set email alerts
|

Snail2 is an Essential Mediator of Twist1-Induced Epithelial Mesenchymal Transition and Metastasis

Abstract: To metastasize, carcinoma cells must attenuate cell-cell adhesion to disseminate into distant organs. A group of transcription factors, including Twist1, Snail1, Snail2, ZEB1, and ZEB2, have been shown to induce epithelial mesenchymal transition (EMT), thus promoting tumor dissemination. However, it is unknown whether these transcription factors function independently or coordinately to activate the EMT program. Here we report that direct induction of Snail2 is essential for Twist1 to induce EMT. Snail2 knockd… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
266
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 353 publications
(287 citation statements)
references
References 43 publications
16
266
4
1
Order By: Relevance
“…Of note, the relative upregulation of SLUG/ SNAIL2 expression in the HER2 gene-amplified JIMT1 cells was comparable to the HER2-negative MDA-MB-231 mesenchymal cells, whereas the HER2-negative MDA-MB-468 basallike cells did not show an increase in the expression of SLUG/ SNAIL2. In a similar manner and in accordance with the ability of SLUG/SNAIL2 and TWIST1 to suppress the epithelial branch of the EMT program redundantly in a cooperative manner, 43 the relative expression of TWIST1 was increased by approximately 100-fold in the trastuzumab-resistant HER2 + SLUG + JIMT-1 cells compared with the trastuzumab-responsive HER2 + SLUG -SKBR3 cells. HER2-negative MDA-MB-468 basal cells showed no increase in the expression of TWIST.…”
Section: Epithelial-to-mesenchymal Transition (Emt) Confers Primary Rmentioning
confidence: 57%
“…Of note, the relative upregulation of SLUG/ SNAIL2 expression in the HER2 gene-amplified JIMT1 cells was comparable to the HER2-negative MDA-MB-231 mesenchymal cells, whereas the HER2-negative MDA-MB-468 basallike cells did not show an increase in the expression of SLUG/ SNAIL2. In a similar manner and in accordance with the ability of SLUG/SNAIL2 and TWIST1 to suppress the epithelial branch of the EMT program redundantly in a cooperative manner, 43 the relative expression of TWIST1 was increased by approximately 100-fold in the trastuzumab-resistant HER2 + SLUG + JIMT-1 cells compared with the trastuzumab-responsive HER2 + SLUG -SKBR3 cells. HER2-negative MDA-MB-468 basal cells showed no increase in the expression of TWIST.…”
Section: Epithelial-to-mesenchymal Transition (Emt) Confers Primary Rmentioning
confidence: 57%
“…In addition, the expression of Snail/Slug and Twist were also increased in Nanog overexpressing HeLa cells. It has been reported that Snail/Slug signaling regulates the EMT process (19). This evidence implies that Snail/Slug and Twist participate in regulating the EMT process to influence the metastasis of HeLa cells.…”
Section: Discussionmentioning
confidence: 81%
“…SNAI2, a member of the snail family of C 2 H 2 -type zinc-finger transcription factors, promotes epithelial-mesenchymal transition and has antiapoptotic activity (48). These data demonstrate that SNAI2 is a direct target of miR-124, and that miR-124-mediated inhibition of SNAI2 is dependent on a conversed motif in the 3'-UTR of SNAI2.…”
Section: Discussionmentioning
confidence: 93%